2014
DOI: 10.1111/bjd.13388
|View full text |Cite
|
Sign up to set email alerts
|

The use of propranolol in the treatment of infantile haemangiomas: an update on potential mechanisms of action

Abstract: Currently, propranolol is the preferred treatment for problematic proliferating infantile haemangiomas (IHs). The rapid action of propranolol has been shown to be especially dramatic in IHs involving dyspnoea, haemodynamic compromise, palpebral occlusion or ulceration. Another remarkable aspect of propranolol treatment revealed that the growth of the IHs was not only stabilized, but also that the improvement continued until complete involution was achieved, leading to a considerable shortening of the natural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 119 publications
(243 reference statements)
2
78
0
7
Order By: Relevance
“…We proceeded based on our previous supposition that the Notch pathway might also contribute to establishing two distinct subpopulations at different steps of angiogenesis in IHs, such as ECs versus pericytes [29,37,38]. We demonstrated that the Jagged1 level was increased in involuting IH tissues [15].…”
Section: Cip1mentioning
confidence: 99%
“…We proceeded based on our previous supposition that the Notch pathway might also contribute to establishing two distinct subpopulations at different steps of angiogenesis in IHs, such as ECs versus pericytes [29,37,38]. We demonstrated that the Jagged1 level was increased in involuting IH tissues [15].…”
Section: Cip1mentioning
confidence: 99%
“…The exact mechanism or mechanisms by which propranolol exerts its influence on BG are not fully understood. It is conceivable that propranolol may block catecholamine-induced lipolysis, glycogenolysis and gluconeogenesis, which may facilitate hypoglycemia in children 25 . Young infants have lower glycogen stores.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] The mechanism of action of b-blockers for treatment of vascular tumors is likely multifactorial, arising from a combination of vasoconstriction, inhibition of angiogenic factors such as VEGF, matrix metalloproteinase-2, matrix metalloproteinase-9, and interleukin-6, and induction of apoptosis. [7][8][9] In this limited case report, the patient had significant, sustained improvement of her facial angiofibromas after laser treatment and twice a day topical timolol 0.5% gel application without reported complications. Importantly, her untreated nose and left cheek served as internal controls.…”
Section: Discussionmentioning
confidence: 78%
“…[7][8][9] Herein we present a patient with TSC whose multiple facial angiofibromas were treated by using a protocol combining full field AFR with pulsed-dye laser. Two weeks before her laser surgery and then restarting on postoperative day 5, topical timolol 0.5% gel was applied twice a day to the patient's right cheek only; this administration protocol is similar to that used for the topical treatment of superficial infantile hemangiomas.…”
mentioning
confidence: 99%